Strategi Diseminasi Inovasi Pertanian dalam Mendukung Pembangunan Pertanian - Kurnia Suci Indraningsih (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2017)
Dissemination of innovation of research results/agricultural assessment is an important communication activity in the process. Problems of dissemination agricultural innovation with technology adoption department, aerial result and socio-economic development of farmers. The gap between ideal conditions and the conditions under construction is an interesting thing to look at. This paper is for the process and implementation of dissemination of agricultural innovation, strategy dissemination of agricultural innovation. This paper is a review of some relevant literature and research results. The strategy of dissemination of agricultural innovation can be divided into two, while at the central and regional levels with the understanding of user innovation and the needs or preferences of users of agricultural innovation. Sources of agricultural innovation at the central level derived from IAARD and as a user are BPPSDMP, technical directorate general, business actors (industry / business / private), and main actors (farmers). The dissemination channels that can be done are dominated through electronic media with extensive coverage and print media (books and journals), as well as some interpersonal media (meeting and meeting forums). The support of facilities and facilities becomes a decisive tool for the user's ability to access agricultural innovation. The source of agricultural innovation at the regional level is BPTP with village extensionists as intermediate users and farmers as end users. The role of extensionists and community leaders as motivators is still dominant at the farm level. Thus dissemination channels can be done through interpersonal media such as demonstration plots, technology titles, field meetings, or group meetings. At the level of the Region that is urgently needed. AbstrakDiseminasi inovasi hasil penelitian dan pengkajian pertanian merupakan aktivitas komunikasi yang penting dalam mendorong terjadinya proses penyebaran dan penerapan teknologi dalam suatu sistem sosial pedesaan. Permasalahan diseminasi inovasi pertanian umumnya terkait dengan kesenjangan adopsi teknologi, kesenjangan hasil dan kendala sosial-ekonomi petani. Kesenjangan antara kondisi ideal dengan kondisi riil dalam implementasi diseminasi inovasi pertanian merupakan hal yang menarik untuk dicermati. Tulisan ini bertujuan mengidentifikasi proses dan implementasi diseminasi inovasi pertanian, dan merekomendasikan strategi diseminasi inovasi pertanian. Tulisan ini merupakan hasil review dari beberapa literatur dan hasil penelitian yang relevan. Strategi diseminasi inovasi pertanian dapat dipilah menjadi dua, yakni di tingkat pusat dan daerah dengan memperhatikan pengguna inovasi dan kebutuhan atau preferensi pengguna inovasi pertanian. Sumber inovasi pertanian di tingkat pusat berasal dari Badan Litbang Pertanian dan sebagai pengguna adalah BPPSDMP, direktorat jenderal teknis, pelaku usaha (industri/pengusaha/swasta), dan pelaku utama (petani). Saluran diseminasi yang digunakan dapat didominasi melalui media elektronik dengan daya jangkau yang luas dan media cetak, serta sebagian berupa media interpersonal (forum pertemuan seperti rapat pimpinan maupun pameran). Dukungan ketersediaan prasarana dan sarana berupa jaringan internet dan perangkatnya menjadi faktor penentu bagi kemampuan pengguna dalam mengakses inovasi pertanian. Sumber inovasi pertanian di tingkat daerah adalah BPTP dengan Penyuluh Pertanian Lapangan sebagai pengguna antara dan petani sebagai pengguna akhir. Peran penyuluh dan tokoh masyarakat sebagai motivator masih dominan di tingkat petani. Dengan demikian, saluran diseminasi yang digunakan dapat didominasi melalui media interpersonal seperti demplot, gelar teknologi, temu lapang, ataupun pertemuan kelompok. Di tingkat daerah dukungan kelembagaan petani yang dinamis sangat diperlukan.